Surgical Treatment of Cervical Spondylotic Myelopathy in the Elderly: Outcomes in Patients Aged 80 Years or Older. Issue 24 (15th December 2018) - Isogai, Norihiro; Nagoshi, Narihito; Iwanami, Akio; Kono, Hitoshi; Kobayashi, Yoshiomi; Tsuji, Takashi; Fujita, Nobuyuki; Yagi, Mitsuru; Watanabe, Kota; Kitamura, Kazuya; Shiono, Yuta; Nakamura, Masaya; et al.
Abstract : Study Design: Retrospective multicenter study. Objective: We aimed to assess the outcomes following posterior cervical decompression for cervical spondylotic myelopathy (CSM) in a large sample of patients older than 80 years. Summary of Background Data: Although age is a predictor of surgical outcomes for CSM, most previous studies have only investigated the effect of age for patients aged 65 to 75 years, and surgical outcomes remain unclear for older patients. Methods: Patients older than 50 years who underwent posterior cervical decompression for CSM were enrolled from 17 institutions. The patients were grouped into a young–old group (<80 yrs old) and an old–old group (≥80 yrs). Clinical information, comorbidities, perioperative complications, Japanese Orthopaedic Association (JOA) scores, Japanese Orthopaedic Association Cervical Myelopathy Evaluation Questionnaire (JOACMEQ), visual analog scale (VAS) scores, and radiographic parameters were compared between the two groups. All patients were followed for at least 1 year after surgery. Results: The young–old and old–old groups included 491 and 77 patients, respectively. The JOA score and quality of life measured by JOACMEQ improved significantly after surgery in both groups. Compared with the young–old group, the old–old group had lower preoperative JOA scores (9.6 vs. 11.0), lower final JOA scores (12.6 vs. 14.0), and lower recovery rates (42% vs. 50%). However, there were no significant differences in perioperative complications or in the VAS scores at the final assessments. The old–old group had a higher mean preoperative sagittal Cobb angle at C2–C5, though this was not statistically significant postoperatively. Conclusion: Posterior decompression surgery is safe and beneficial for patients older than 80 years with CSM, despite having a more limited neurological recovery compared with younger patients. Level of Evidence: 3